Electrophoretic methods for fractionation of humic and fulvic acids - Curvetto, N.R.; Balmaceda, N.A.; Orioli, G.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Humic and fulvic acids extracted from Bovizont A of a Brunizem sample with dilute sodium hydroxide solution were separated by isotachophoresis and electrofocusing on a polyacrylamide gel. Ampholine carrier ampholytes ranging in size from 3 to 10 were used as a spacer and to form a natural pH gradient. Different pH, pore size and gel geometry were tested during isotachophoresis. The number of subfractions obtained by isotachophoresis on a 3.75% polyacrylamide gel, pH 6.7, was 10 for fulvic acid and 13 for humic acid. When the polarity was reversed, four subfractions separated on the running gel. Electrofocusing in 12-cm-long tubes with 3.75 percent polyacrylamide gel showed a large number of subfractions distributed in pH values ​​between 3.7 and 7.5 for AF and between 4.5 and 7.5 for AH. The position of the bands in the natural pH gradient is considered an indication of their Ka value.